Analisis Determinan Kemiskinan Provinsi Daerah Istimewa Yogyakarta Tahun 2015 - 2020 - Nabilawaty, Risma Cindy; Hutajulu, Dinar Melani (Jurusan PIPS FKIP UMMY Solok, 2021)
Poverty is a serious obstacle to economic development in a country, especially developing countries. Poverty has the potential to generate a wide range of issues in many sectors of the economy. In fact, there are various other factors that can affect poverty. This contemplate directs to psychoanalyse the constituents that influence the impoverishment commensurate of DI Yogyakarta responsibility in 2015-2020. Fountain-heads of collections euphemistic pre-owned therein contemplate are less important collections from the fundamental Statistics superintendence (BPS) and accompanying instrumentalities and literature. The psychoanalysis disposition euphemistic pre-owned is venire collections retrogression analysis. Economic growth and the Human Development Index (HDI) have a negative but substantial i on poverty levels in Yogyakarta Province, according to the findings of the study. Factors such as the unemployment rate also have an influence on the poverty level in Yogyakarta Province, although it shows a relatively small impact. Yogyakarta Province's population growth and decline have a positive and substantial impact on the region's poverty level.